Disease Self-Efficacy and Health-Related Quality of Life in Adolescents With Sickle Cell Disease. Issue 2 (March 2020) - Goldstein-Leever, Alana; Peugh, James L.; Quinn, Charles T.; Crosby, Lori E.
Abstract : Adolescents and young adults (AYA) with sickle cell disease (SCD) are at risk for poor health-related quality of life (HRQOL). Research suggests that vulnerability factors (eg, disease severity) and self-management resources (eg, disease self-efficacy) jointly impact health outcomes, including HRQOL; however, this has not been studied among AYA with SCD. This study examined the relationship between disease self-efficacy, HRQOL, and disease severity in AYA with SCD. HRQOL was positively correlated with disease self-efficacy and negatively correlated with disease severity. Disease self-efficacy and severity accounted for 35% of variance in HRQOL. Findings support the impact of disease self-efficacy on HRQOL.